2014
DOI: 10.1080/19476337.2014.919962
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage and insect infestation on the technological properties of wheat

Abstract: The objective of this study was to evaluate how storage and Sitophilus granarius L. infestation affects technological properties of wheat samples. Wheat samples were infested with S. granarius at a rate of 2 adults/kg, and stored for 6 months at 30 ± 1°C and 70 ± 5% relative humidity. At monthly intervals, samples of wheat were collected and evaluated for insect population, and physical, chemical, and physicochemical properties. Additionally, white flour samples obtained from these wheat samples were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 14 publications
6
21
0
3
Order By: Relevance
“…The increases in the protein might be the result of the insect body parts and metabolic waste of insects. The decrease in gluten content in the infested samples was reported by (Keskin and Ozkaya., 2015)who showed that the reduction in gluten content due to the fact that gluten was brittle and disintegrated easily. A portion of it was lost during washing, and therefore, the gluten yield was lowered.…”
Section: Wheat Properties During Storagesupporting
confidence: 72%
“…The increases in the protein might be the result of the insect body parts and metabolic waste of insects. The decrease in gluten content in the infested samples was reported by (Keskin and Ozkaya., 2015)who showed that the reduction in gluten content due to the fact that gluten was brittle and disintegrated easily. A portion of it was lost during washing, and therefore, the gluten yield was lowered.…”
Section: Wheat Properties During Storagesupporting
confidence: 72%
“…Kemunculan kutu beras tersebut bisa diakibatkan karena kandungan beras yang kurang baik sehingga mudah rapuh ataupun tempat penyimpanan yang lembab [4]. Keberadaan kutu beras tersebut menyebabkan rusaknya beras berupa beras berubah menjadi serbuk maupun berlubang serta beras mengalami penurunan bobot [5][6][7].…”
Section: Pendahuluanunclassified
“…Beras yang memiliki kandungan protein rendah akan menghasilkan aleuron yang lebih sedikit sehingga cepat rusak. Kerusakan beras tersebut bisa ditandai dengan adanya pelapukan yang memicu munculnya kutu beras [4] dan beras akan berubah bentuk menjadi serbuk [6]. Semakin tinggi kandungan protein maka aleuron yang dihasilkan semakin banyak dan kutu yang menghinggapi beras tersebut semakin sedikit karena pada dasarnya kutu beras tidak suka terhadap aleuron dan beras dengan kandungan protein tinggi.…”
Section: Gambar 1 Grafik Pertambahan Jumlah Kutu Beras Dari Kelompokunclassified
“…The qualitative and quantitative damage associated with this type of infestation causes estimated losses of several million tons of wheat every year, accounting for millions of dollars . Most of the stored‐wheat insects preferentially eat out grain embryos and feed on the starchy endosperm, thereby lowering the end‐use quality of the flour . Rhyzopertha dominica (lesser grain borer) is a major pest found in stored wheat, named for its ability to bore holes over the grain surfaces, which may expedite infestation by a secondary pest .…”
Section: Introductionmentioning
confidence: 99%
“…1 Most of the stored-wheat insects preferentially eat out grain embryos and feed on the starchy endosperm, thereby lowering the end-use quality of the flour. 2 Rhyzopertha dominica (lesser grain borer) is a major pest found in stored wheat, named for its ability to bore holes over the grain surfaces, which may expedite infestation by a secondary pest. 3 R. dominica is one of the most deleterious insects, important to control because of its ability to bore deeper into the grain mass as compared to other stored grain pests.…”
Section: Introductionmentioning
confidence: 99%